Identification of High School Students' Success in Representing Logarithm Function Graphs - Amalia Chamidah; Lydia Lia Prayitno; Ika Kurniasari (Department of Mathematics Education, Faculty of Teacher Training and Education, Wisnuwardhana University of Malang, 2022)
A visual presentation is a form of representation that helps students express the equations of logarithm functions. This is a qualitative descriptive study to identify the success of high school students in representing graphs of logarithm functions. Four students of SMA Hang Tuah 4 Surabaya became the research subjects. Data were collected through the researcher as the main instrument, TMGFL questions, and interview guidelines. The data were analyzed by researchers using the view points of the stages of translation of representation from verbal form to graphs. The subject's success in representing the graph of a logarithm function is based on the accuracy of reading the information, translating the equation into a simple form, determining the coordinates of the points traversed by the graph, connecting the points to form a graph, and verifying it. This study has a weakness, students who succeed in describing graphs of logarithm functions, for that further research is needed to identify the failures of students who do not succeed in representing logarithm functions and find solutions.